Impact of Sharia Financial Literacy on MSME Interest in Using Sharia Financial Products in Palopo - Azzahra, Isramiyanti; Salju, Salju; Antong, Antong (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine the influence of Islamic financial literacy on the interest in using Islamic financial products among Micro, Small, and Medium Enterprises (MSMEs) in Palopo City. Methodology: A quantitative survey approach was employed using purposive sampling. Data were collected from 56 MSME respondents via online questionnaires and analyzed using linear regression with SmartPLS 4. Results: The analysis revealed that Islamic financial literacy—comprising knowledge of Islamic financing, investment, and insurance—has a positive and significant effect on the interest in using Islamic financial products. Findings: The study confirms that greater understanding of Islamic finance principles enhances MSMEs’ willingness to engage with Sharia-compliant financial services. Novelty: This research provides empirical evidence from MSMEs in a regional Indonesian context, focusing specifically on the role of financial literacy in shaping Islamic financial product adoption. Originality: Unlike prior studies, this work integrates multiple dimensions of Islamic financial literacy and targets the under-researched MSME sector in Palopo City. Conclusions: Improving Islamic financial literacy is critical to encouraging ethical financial decisions and increasing the adoption of Sharia-compliant products among MSMEs. Type of Paper: Quantitative Empirical Research Paper.